일반화학 및 혈액 검사를 위한 LOINC 적용 지침 - 박근열; 유혜진; 김민선; 오예진; 유신애; 조은정; 김솔잎; 정재우; 윤여민; 이영경; 전사일; 진단검사의학재단 표준화사업부; et al. (Laboratory Medicine Online, 15(1), 2025)
This document aims to provide guidelines and examples for mapping the appropriate Logical Observation Identifiers Names and Codes (LOINC) for general chemistry and hematology tests for in vitro diagnostic manufacturers, laboratory professionals, and those involved with medical records or hospital information systems who need to map test names to LOINC terminology. The guidelines cover general principles for selecting the correct laboratory LOINC mapping, with some specificity for general chemistry and hematology tests. These guidelines can facilitate interoperability of test results between institutions in Korea and thereby improve patient safety. 이 적용 지침은 논리적 관찰 식별자 이름 및 코드(LOINC) 용어 매핑에 관계된 진단검사의학 전문의, 임상병리사, 체외진단의료기기 제조업체, 보건의료정보관리사 또는 병원정보시스템 관계자를 위해 일반 화학 및 혈액 검사에 적합한 LOINC 코드를 매핑하기 위한 지침과 예시를 제공하는 것이다. 이 적용 지침은 올바른 진단검사의 LOINC 매핑을 선택하기 위한 일반적인 원칙을 다루며, 일반 화학 및 혈액 검사에 대한 몇 가지 구체적인 내용을 담았다. 이 적용 지침이 국내 기관 간 진단검사 결과의 상호운용성을 촉진하여 환자 안전을 개선할 수 있기를 기대한다.